A critical analysis of the prostitution phenomenon, drawing examples from selected African countries: a literature review. - Mafa, Itai; Kang’ethe, S.M. (Kamla-Raj Enterprises, 2020)
An uncontested prevalence of the prostitution phenomenon around the globe has attracted centrestage attention causing a heated debate around its legal grounds. This paper, through a literature review attempts to discuss the policy environment underpinning the dynamics of prostitution. The following factors have been identified as possible push factors to prostitution: paucity of economic resources, increased phenomenon of matrifocal families; cultural attrition and increased state of moral decadence. Further, discussion on whether to legalise or criminalise prostitution has been pertinent, with forces in support of criminalizing the practice leaning on the phenomenon’s impact to the practitioners’ health and psychological well-being; and the fact that most societies consider it both illegal and immoral. The paper ends up by making the following proposals: Improving policies that foster economic development; strengthening empowerment programmes that will facilitate the practitioners from exiting from the practice; educating the masses on the interplay between prostitution and prevalence of HIV/AIDS; as well as fixing a proper trademark on prostitution.